Analisis Kebijakan dalam Pendidikan Dasar dan Menengah dalam Perspektif Pemerataan Mutu - Sarah Puspita; Mauliatur Rohmah; Qomaruddin Qomaruddin (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Education is a fundamental right of every citizen guaranteed in the Indonesian constitution, particularly in the 1945 Constitution of the Republic of Indonesia, Article 31. The Indonesian government has issued various policies to improve the quality of primary and secondary education while ensuring equitable access and quality across all regions. Nevertheless, the disparity in education quality between urban and rural areas, as well as between western and eastern regions of Indonesia, remains a serious challenge. This article aims to analyze primary and secondary education policies from the perspective of quality equity, identify factors hindering policy implementation, and formulate strategic recommendations for improvement. The study uses a literature review method with a descriptive-analytical approach through the examination of regulations, government reports, and previous research findings. The analysis results show that policies such as the School Operational Assistance (BOS), the Indonesia Smart Program (PIP), and the Merdeka Curriculum have improved access to education and learning flexibility. However, disparities in teacher distribution, limited infrastructure, as well as weak oversight and policy evaluation remain major obstacles in equalizing the quality of education. Keywords: Education Policy, Quality Equalization, Primary Education, Secondary Education